Evaluation of physicochemical and Microbiological parameters in the remediation of soils contaminated by petroleum hydrocarbons using organic compost - Camila Camolesi Guimarães; Leonides Guireli Netto; Alexandre Muselli Barbosa (Discover Geoscience)
Abstract The presence of contaminated sites is a critical issue in many places around the world, both in developed and developing countries. São Paulo, the most populous state in Brazil, has more than 6,000 registered contaminated sites. The main pollutants found are automotive fuels, especially hydrocarbons derived from petroleum. Among the various remediation techniques available, the addition of organic compost to contaminated soil stands out as an approach that incorporates sustainability principles. This compost can be used for bioremediation, as it favors and stimulates the growth of different populations of microorganisms capable of degrading a variety of contaminants. In Brazil and other countries with a tropical climate, there is great potential for the use of compost in remediation, due to the climatic characteristics, the physical-chemical properties of the soils and the significant amount of organic waste generated in the country. This study investigated the application of organic compost in the remediation of soils contaminated by petroleum hydrocarbons in a laboratory environment. To this end, an Oxisol was artificially contaminated with diesel oil (O1) and a mixture of bunker fuel oil, diesel and kerosene (O2), in two concentrations (10 g/kg and 100 g/kg), in addition to the application of organic compost, in two proportions (1:0.1 and 1:0.5). The results showed that, at the end of the experiment, the concentrations of total petroleum hydrocarbons were reduced by up to 90% in the diesel oil treatments over 91 days. The presence of organic compost led to an increase in the levels of organic matter, volatile solids, pH and electrical conductivity, as well as improving soil structure and increasing the development of microorganism populations. In this way, compost acted as a source of energy for the soil’s microorganisms and as a source of new metabolically active microorganisms, contributing to increased biodegradation rates. The results of this study indicate that the addition of organic compost is an effective strategy for the remediation of soils contaminated by petroleum hydrocarbons, promoting improvements in the physical, chemical and biological conditions of the soil and, therefore, can be a sustainable technique with positive environmental, social and economic impacts.